2023
DOI: 10.54371/jiip.v6i2.1683
|View full text |Cite
|
Sign up to set email alerts
|

Penguatan Pemahaman Matematika dengan Media GeoGebra Classroom Materi Bangun Ruang Sisi Datar pada Siswa Kelas 8 SMP/MTs

Abstract: Kemampuan siswa dalam memahami materi matematika yang bersifat abstrak masih sangat kurang terutama pada materi Tiga Dimensi Bangung Ruang Sisi Datar. Salah satu inovasi yang digunakan adalah memanfaatkan media pembelajaran yang menarik menggunakan Media GeoGebra Classroom sebagai penguatan pemahaman konsep matematika siswa. Penelitian ini menggunakan metode Research and Depelopment dengan menggunakan model ADDIE untuk mengembangkan media GeoGebra Classroom. Subjek penelitian ini adalah siswa MTs/SMP kelas VII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…Mathematical concepts refer to newly formed understandings arising from thinking, encompassing definitions, meanings, characteristics, essence, and the core/essence of mathematical content (Boediono, 2009). In line with the opinion mentioned above, according to Sadikin et al (2017), conceptual understanding is the ability demonstrated by students to comprehend the definitions, meanings, characteristics, essence, and core/essence of mathematics, as well as the ability to select appropriate procedures to solve problems (Apriliyana et al, 2023). Thus, mastery of mathematical concepts is the foundation for solving mathematical problems.…”
Section: Introductionmentioning
confidence: 83%
“…Mathematical concepts refer to newly formed understandings arising from thinking, encompassing definitions, meanings, characteristics, essence, and the core/essence of mathematical content (Boediono, 2009). In line with the opinion mentioned above, according to Sadikin et al (2017), conceptual understanding is the ability demonstrated by students to comprehend the definitions, meanings, characteristics, essence, and core/essence of mathematics, as well as the ability to select appropriate procedures to solve problems (Apriliyana et al, 2023). Thus, mastery of mathematical concepts is the foundation for solving mathematical problems.…”
Section: Introductionmentioning
confidence: 83%
“…Dari beberapa penjelasan tersebut dapat disimpulkan bahwa pemahaman konsep adalah kompetensi yang ditunjukkan oleh siswa dalam mengaplikasikan konsep sesuai dengan prosedur yang tepat dalam menyelesaikan masalah. Dikemukakan oleh Apriliyana et al (2023) bahwa keterampilan siswa dalam memahami suatu konsep pada materi matematika sebagai bukti bahwa siswa telah berhasil setelah menerima pembelajaran.…”
Section: Pendahuluanunclassified
“…Matematika merupakan ilmu yang memegang peranan penting dalam berbagai aspek kehidupan dan tidak dapat dipisahkan dari kehidupan. Menurut Apriliyana et al, (2023) (mathematical content) dan standar proses (mathematical process) (Izzah et al, 2019).…”
Section: Pendahuluanunclassified